Effect of fermentation on the organosulfur compound profile and antibacterial activity of black garlic (Allium sativum) extract - Putri, Adela Syiddah; Mufalla, Siti Nur; Rusdi, Hanumi Oktiyani; Wonorahardjo, Surjani; Suharti, Suharti (Eclética Química, 2026)
Black garlic is a derivative product of garlic that offers even more health benefits. During fermentation, various chemical reactions alter the chemical composition of garlic. In this study, the organosulfur compound profile of black garlic was analysed using GC-MS and LC-MS, and its antibacterial activity was also tested. In the initial stage, garlic was fermented at a constant temperature of 60 °C for 24 days. The GC-MS analysis revealed four organosulfur compounds. Meanwhile, the LC-MS analysis detected 16 distinct organosulfur compounds and their quantities at each fermentation stage. One organosulfur compound was consistently detected in LC-MS analysis across all fermentation stages. Antibacterial activity was tested using the paper disc diffusion method against S. aureus and E. coli bacteria. The research findings showed that the most effective black garlic in killing bacteria was fermented for 18 days. This was evident from the largest and most stable diameter of inhibition zones.